Epistemology naturalized: Quine's intervention in the debate concerning the problem of knowledge - Michael Sunday Sasa (International Journal of Humanities and Innovation (IJHI), 2018)
The present paper attempts critical navigation of what could be referred to as the Quinean Intervention in the debate concerning knowledge. This problem easily represents the central concern of traditional epistemology, particularly since the modern period. Its retrospective statement finds expression in the ancient definition of knowledge as justified true belief (JTB). Among the problems easily identified with the traditional conception of knowledge is exhaustive or conclusive justification, which is to form the base of the structure of knowledge. Philosophers across the spectrum of discourse have risen to respond to the problem. Prominent among the position is foundationalism and coherentism as theories of justification. However, these theoretical representations are never able to proffer the conclusive justification condition; thus, epistemology's traditional problem has mainly remained unresolved. Philosophers across the board have therefore proffered several alternatives. One of such is the project to naturalize epistemology – a program famously identified with W.V.O. Quine. The paper examines Quine's position to move epistemology from philosophy to psychology. This project, the paper argues, stripped epistemology of its normative status. Therefore, it cannot be regarded as a philosophical proposal, as philosophy is essentially prescriptive, not descriptive, matters of ought not matters of is or matters of values not matters of fact. For this reason, the paper rejects the Quinean project, describing it as a non-epistemic response to an epistemological problem. The paper employs the philosophical method of analysis, clarification, and criticism, combining this with reconstruction and clarity.